2021
DOI: 10.5604/01.3001.0015.0427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for prognosticating blunt trauma chest

Abstract: <b>Introduction:</b> Blunt trauma chest contributes to significant number of trauma admissions globally and is a cause of major morbidity and mortality. Many scoring systems and risk factors have been defined in past for prognosticating blunt trauma chest but, none is considered to be gold standard. </br> <b>Aim:</b> This study was conducted to reassess the significance of available scoring systems and others indicators of severity in prognosticating blunt trauma chest patients. &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Ten studies demonstrated a higher risk of mortality in patients with three or more fractured ribs, when compared with patients with less than three rib fractures 6 7 13 33 38 40 45 47 70 71. Other studies reported an increasing risk of mortality with each additional rib fracture,2 34 39 43 66 72 four or more rib fractures,51 five or more rib fractures,20 35 55 six or more rib fractures,50 eight or more42 and multiple rib fractures (unspecified number) 53. Five studies found no association between number of rib fractures and increased risk of mortality 56 58 73–75…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies demonstrated a higher risk of mortality in patients with three or more fractured ribs, when compared with patients with less than three rib fractures 6 7 13 33 38 40 45 47 70 71. Other studies reported an increasing risk of mortality with each additional rib fracture,2 34 39 43 66 72 four or more rib fractures,51 five or more rib fractures,20 35 55 six or more rib fractures,50 eight or more42 and multiple rib fractures (unspecified number) 53. Five studies found no association between number of rib fractures and increased risk of mortality 56 58 73–75…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies demonstrated an increasing risk of mortality per additional year of age5 54–56 and others with an additional decade 2 14 57. In 14 studies age was not found to be a statistically significant risk factor for increased mortality,3 37 58–69 however it is worth noting that 4 of these studies used aged 45 years or more as the cut-off for increased risk 58 63 67 69…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation